2020
DOI: 10.3390/ijms21228651
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies to Reduce the Toxicity of Misfolded Protein Oligomers

Abstract: The aberrant aggregation of proteins is implicated in the onset and pathogenesis of a wide range of neurodegenerative disorders, including Alzheimer’s and Parkinson’s diseases. Mounting evidence indicates that misfolded protein oligomers produced as intermediates in the aggregation process are potent neurotoxic agents in these diseases. Because of the transient and heterogeneous nature of these elusive aggregates, however, it has proven challenging to develop therapeutics that can effectively target them. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 253 publications
(323 reference statements)
0
26
0
Order By: Relevance
“…Currently available treatments for Parkinson's disease are aimed at managing symptoms, but they do not stop the progression of the disease (253)(254)(255)(256). Therapeutic interventions targeting α-synuclein aggregation and interactions offer promising opportunities for developing disease-modifying drugs (257). Since post-translational modifications modify how α-synuclein aggregates and interacts with lipid membranes, they offer promising opportunities for the treatment of Parkinson's disease and related synucleinopathies.…”
Section: Therapeutic Targeting Of Post-translational Modifications Of α-Synucleinmentioning
confidence: 99%
“…Currently available treatments for Parkinson's disease are aimed at managing symptoms, but they do not stop the progression of the disease (253)(254)(255)(256). Therapeutic interventions targeting α-synuclein aggregation and interactions offer promising opportunities for developing disease-modifying drugs (257). Since post-translational modifications modify how α-synuclein aggregates and interacts with lipid membranes, they offer promising opportunities for the treatment of Parkinson's disease and related synucleinopathies.…”
Section: Therapeutic Targeting Of Post-translational Modifications Of α-Synucleinmentioning
confidence: 99%
“…Numerous neurodegenerative diseases are characterized by a complex pathophysiology that has made highly challenging the identification of targets for drug discovery and the development of clinical treatments (Cummings et al, 2014;Knowles et al, 2014;Chiti and Dobson, 2017). The aberrant misfolding, aggregation, and deposition of amyloid-β peptide (Aβ) and α-synuclein (αS) into pathological aggregates plays a central role in Alzheimer's disease (AD) and Parkinson's disease (PD), and recent evidence has demonstrated that oligomeric intermediates in the process of fibril formation are especially deleterious toward neuronal cells (Kreiser et al, 2020). These aggregates may, therefore, play a causative role in the onset and propagation of protein misfolding diseases throughout the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, incubation with small therapeutic molecules, such as the aminosterol squalamine, found previously to be protective in cell models and in transgenic PD strains of C. elegans by binding to the cell membrane and displacing oligomeric α-synuclein 56 , suppresses dramatically the oligomeric toxicity in this system. Given that the populations of oligomers produced during aggregation reactions is highly heterogeneous in conformational and physico-chemical properties 68 , the results that we have reported www.nature.com/scientificreports/ for HypF-N and α-synuclein oligomers provide further insight into the relationship between these properties and cytotoxicity 25,53,69,70 .…”
Section: Discussionmentioning
confidence: 79%